Analisis Yuridis Kedudukan Barang Bukti yang Diperoleh Melalui Penyidikan yang Diduga Melanggar Kode Etik - Maergy Putri Lianti; Anza Ronaza Bangun (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This research analyzes the normative juridical legal status of evidence obtained during the investigation of corruption crimes, with allegations of violations of the code of ethics and procedures by investigators. The central issue examined is the dilemma between upholding due process of law (fair legal process) and the pursuit of material truth, which reflects the Fruit of the Poisonous Tree Doctrine. The research method is normative juridical, using a statute approach and conceptual approach. Primary data sources include the Criminal Procedure Code (KUHAP), the Law on the Eradication of Corruption Crimes, and Supreme Court jurisprudence decisions. The research findings indicate that Indonesia's criminal procedural law adheres to the principle of absolute admissibility (rule of admissibility), where violations of investigators' code of ethics are generally handled through internal disciplinary mechanisms, without automatically invalidating the validity of evidence. Evidence remains valid if it meets the formal and material requirements under Article 184 of the KUHAP. However, there are indications that judges are beginning to consider serious ethical violations that infringe on human rights to reject the admissibility of evidence, as a measure to maintain the integrity of law enforcement. This research recommends the harmonization of regulations that clearly regulate the tolerance limits for violations of the code of ethics and their impact on the validity of evidence, to provide legal certainty and enhance the professionalism of law enforcement officials.